A educação de adultos como socialização: Hannah Arendt versus Paulo Freire - Whitaker, Dulce Consuelo Andreatta [UNESP]; Souza, Marinaldo Fernando de [UNESP] (My University, 2014)
This paper analyzes data under diametrically opposed theoretical frameworks. Encouraged by the sudden and recent popularity of Hannah Arendt, we decided to submit the data of a already presented dissertation to a “new” reference, extracted from Arendt’s famous text on the education crisis in the United States in the 1950. Data had been interpreted in the light of Paulo Freire’s epistemology. In further analyzes, from Arendt, our interpretations gained even more strength. However, in the final comparison between the two thinkers stand out irreconcilable differences: For Arendt, it is impossible to educate adults and the world of education should be detached from the world of politics, since the responsibility of the educator is based on tradition and authority while for Freire is indeed possible to educate adults and the responsibility of the educator – as in Sartre – leads to freedom. Our conclusion is to be possible the social education of adults if we educate ourselves with them in a dialogic relationship.

Este texto analisa dados sob referenciais teóricos diametralmente oposto. Estimulados pela repentina e recente popularidade de Hannah Arendt, resolvemos submeter os dados de uma dissertação já defendida a um “novo” referencial, extraído do famoso texto de Arendt sobre a crise da educação nos Estados Unidos nos anos 1950. Os dados haviam sido interpretados à luz da epistemologia de Paulo Freire. Em novas análises, a partir de Arendt, nossas interpretações ganharam ainda mais força. No entanto, na comparação final entre os dois pensadores, destacam-se diferenças irreconciliáveis: Para Arendt, é impossível educar adultos e o mundo da educação deve ser desvinculado do mundo da política, já que a responsabilidade do educador se baseia na tradição e na autoridade, enquanto para Freire é possível sim educar adultos e a responsabilidade do educador – tal como em Sartre – leva à liberdade. Concluímos ser possível a educação social de adultos se, numa relação dialógica, nos educarmos com eles.
Keywords: Adult education; Dialogic education; Paulo Freire; Hannah Arendt; Educação de adultos; Educação dialógica; Paulo Freire; Hannah Arendt